Skeletal Manifestations, Bone Pain, and BMD Changes in Albanian Type 1 Gaucher Patients Treated with Taliglucerase Alfa - Virtut Velmishi; Erjon Troja; Marjeta Tanka; Donjeta Bali; Ermira Dervishi; Afërdita Tako; Laurant Kollcaku; Paskal Cullufi (Journal of Osteoporosis)
Gaucher disease is a rare, genetic lysosomal disorder leading to lipid accumulation and dysfunctions in multiple organs. Bone involvement is one of the most prevalent aspects of Gaucher disease. Pain, disability, and reduced quality of life remain the most frequent characteristics of bone involvement in Gaucher patients. Patients and Method. In this study, we will take into consideration data from 24 patients diagnosed with type 1 Gaucher disease. We followed them closely for six years in progress. At baseline, all patients started therapy with taliglucerase alfa at a mean dosage of 45 UI/kg; later, during the study, two of them switched their cure toward velaglucerase alfa. Before baseline evaluations, 12 patients had been treated with imiglucerase at variable duration times. At baseline, we performed an X-ray of long bones and the spine, and each year, different standard assessments were performed, such as bone pain, MRI of the vertebral spine and pelvis, and DEXA for bone density. Four patients left the study for various reasons, two of them at baseline and two others during year 3 (FU3). Results. At baseline, we had 8 children and 16 adults. The average age was 28.7 ± 16.5 SD years. The most frequent skeletal manifestations in our patients were reduction of tibial femoral space (40%), osteonecrosis (36%), and body vertebral reduction (32%). At baseline, 15 patients presented with bone pain to different degrees. Over the years, bone pain in our patients had a gradual improvement. The most dramatic bone pain improvement was seen in a patient who presented bone crises. Another impressive finding was a significant BMD improvement during six years of treatment. Our study showed a significant improvement in BMD comparing FU5 and baseline values (p = 0.0007). Especially children demonstrated a significant improvement in BMD (p = 0.00061) compared to adults (p = 0.3673). Mean BMD change was more indicative in switched patients (p = 0.0142) compared to naïve patients (p = 0.147). Conclusions. Skeletal manifestations are very different in Gaucher type 1 patients. In our study, as a result of long-term evaluations, it was noticed that the most frequent skeletal manifestation was a reduction of tibiofemoral space. Bone pain has gradually improved in all patients. Also, BMD values have been enhanced over six years of treatment, especially in children.